Ion composition in Titan's exosphere via the Cassini Plasma Spectrometer I: T40 encounter. Issue 1 (19th January 2015) - Woodson, A. K.; Smith, H. T.; Crary, F. J.; Johnson, R. E.
Abstract We investigate the complex interaction between Saturn's magnetosphere and Titan's upper ionosphere using ion data acquired by the Cassini Plasma Spectrometer (CAPS) during the T40 encounter. Bounds on ion‐group abundances at altitudes between 2733 and 12, 541 km are determined by fitting mass spectra with model functions derived from instrument calibration data. The spectra are dominated by H+, H2+, H3+, and two hydrocarbon groups with mass ranges 12–19 and 24–32 amu, respectively. Notably, this constitutes the first reported observation of H3+ in Titan's exosphere. These measurements are discussed in the context of data from the CAPS electron spectrometer (ELS) and the Ion and Neutral Mass Spectrometer (INMS), which fortuitously sampled the ionospheric outflow during the T40 encounter at altitudes between 2225 and 3034 km. The CAPS data reveal a composition that is constitutively similar to that sampled by INMS, with hydrocarbon ions first observed as far as 11, 000 km from Titan and increasing in density by more than an order of magnitude along Cassini's inbound trajectory. In addition, we juxtapose the CAPS ion data with numerical results from three different interaction models and show that it is consistent with the location of the field‐draping boundary described by Ulusen et al. (2012) and the Saturnward ion tail predicted by Sillanpää et al. (2006).